Development of a real-time eye movement-based computer interface for communication with improved accuracy for disabled people under natural head movements - Chhimpa, Govind Ram; Kumar, Ajay; Garhwal, Sunita; Dhiraj (Journal of real-time image processing, 2023)
In recent years, the scarcity of effective communication systems has been an essential issue for disabled people [physically disabled, locomotor disability, and amyotrophic lateral sclerosis (ALS)] who cannot speak, walk, or move their hands. The lives of disabled people depend on others for survival, so they need assistive technology to live independently. This research paper aims to develop an efficient real-time eye-gaze communication system using a low-cost webcam for disabled persons. This proposed work developed a Video-Oculography (VOG) based system under natural head movements using a 5-point user-specific calibration (algorithmic calibration) approach for eye-tracking and cursor movement. During calibration, some parameters are calculated and used to control the computer with the eyes. Additionally, we designed a graphical user interface (GUI) to examine the performance and fulfill the basic daily needs of disabled individuals. The proposed method enables disabled persons to operate a computer by moving and blinking their eyes, similar to a typical computer user. The overall cost of the developed system is low (Cost < $50, varies based on camera usage) compared to the cost of various existing systems. The proposed system is tested with disabled and non-disabled individuals and has achieved an average blinking accuracy of 97.66%. The designed system has attained an average typing speed of 15 and 20 characters per minute for disabled and non-disabled participants, respectively. On average, the system has achieved a visual angle accuracy of 2.2 degrees for disabled participants and 0.8 degrees for non-disabled participants. The experiment’s outcomes demonstrate that the developed system is robust and accurate.